Screen-based sedentary behaviors but not total sedentary time are associated with anxiety among college students - Huang, Tao; Zheng, Kefeng; Li, Shiyuan; Yang, Yanxiang; Kong, Lingxuan; Zhao, Ying (Frontiers in Public Health, 2022)
Objective The purpose of the study was to investigate the associations of device-measured total sedentary time and screen-based sedentary time with anxiety in college students. Methods Three hundred and twenty-one college students (mean age = 19.72 ± 1.18, 55.8% females) were recruited from Shanghai, China. Total sedentary time was objectively measured using accelerometry, while screen-based sedentary time was self-reported. Anxiety symptom was evaluated using the Self-Rating Anxiety Scale. Linear regression modeling was used to assess the associations of total sedentary time and screen-based sedentary time with anxiety symptom. Results Accelerometer-assessed total sedentary time was not associated with anxiety symptom. Prolonged sedentary time on TV and movie viewing (>2 h on weekdays) and social media using (>2 h on weekdays and weekend) were associated with a higher level of anxiety. However, time on video gaming and recreational reading was not associated with anxiety symptom. Conclusion The findings indicated that screen-based sedentary behaviors but not total sedentary time were associated with anxiety symptom among college students. The associations of screen-based sedentary behaviors with anxiety symptom varied by the types of screen time.